The Center-periphery Dilemma and the Issue of Equity in Regional Development - Daniel Shefer (European Regional Science Association (ERSA), 2011)
Different regions are endowed with production factors and characteristics that offer different opportunities for specialization, which can be transform to a regional comparative advantage. Many outlying regions (peripheral regions) suffer from a high rate of unemployment, low level of per capita income and net out migration. Outlying areas attract less investment in comparison to central regions. This is because of the low marginal productivity of factors of production in the outlying areas. In order to alleviate these hardships, inflicted on outlying regions, central governments often devise incentive and investment programs whose main objective is to reduce the gap between regions in the country and thus reduce regional inequalities. To attract high tech industries to outlaying regions is now in vogue. In reality we observe a distinct geographical distribution between centers of R&D and large mass production plants. This is due primarily to agglomeration economies and industrial cluster in central regions. Mass production, because of their needs for a large number of relatively unskilled labors gravitates towards the edge of Metropolitan regions and the outlying areas. But then their contribution to the wellbeing of the population in these regions is limited. Public/private investment in large scale facilities (or infrastructures), like highways and railways, Technological Incubators, R&D Centers, universities and hospitals, are among the projects proposed in order to facilitates economic growth in outlying areas. However investing in these projects is not necessarily the panacea for outlaying areas. Because of scarce resources it is paramount to select the most cost-effective program which will take into account the profile of the region under consideration, its natural endowments, and the administrative and political structure of the local government and its ability, together with the region's population, to turn the chosen program to a success. In this paper we critically discuss the spatial implications of selected public investment programs design to facilitate the development of peripheral regions.
Keywords: 330